Analysis of the Impact of Capital Expenditures, Expenditures on Goods and Services, DAK, and DBH on Poverty - Rifati, Kamilatur; Nurul Badriyah (Journal of Development Economic and Social Studies, 2026)
The still relatively high poverty rate in Aceh Province highlights the urgency of evaluating the effectiveness of local government spending as a fiscal policy instrument for improving public welfare. This study aims to analyze the impact of capital expenditures, goods and services expenditures, the Special Allocation Fund (DAK), and the Revenue-Sharing Fund (DBH) on poverty levels. The study employs a quantitative approach using panel data regression on 23 regencies/cities in Aceh Province during the 2018–2023 period, utilizing secondary data from the Central Statistics Agency and the Directorate General of Fiscal Balance. The results indicate that capital expenditure and DAK have no effect on poverty, whereas expenditure on goods and services and DBH have a negative and significant effect. These findings suggest that expenditures oriented toward public services are more effective in reducing poverty. The implications of this study emphasize the importance of optimizing the allocation and effectiveness of local government spending to ensure it is more targeted in supporting sustainable poverty reduction.